Gender Sensitive Planning, Monitoring and Evaluation in Agricultural Water Management - Gautam, Suman Rimal (World Bank, Washington, DC, 2016)
Agricultural water management projects that take an inclusive, participatory gendersensitive approach at all levels of the project cycle help increase project effectiveness and improve account of livelihood concerns of women and the rural poor. Participatory planning methods; creation of genderspecific indicators; continuous monitoring; and beneficiary-led impact assessment are key features of this approach.